2020
DOI: 10.1186/s12903-020-01092-9
|View full text |Cite
|
Sign up to set email alerts
|

A combination of kissing molars, maxillary bilateral supernumerary teeth and macrodontia: a rare case report

Abstract: Background: Supernumerary teeth (ST) is defined as an additional number of teeth compared to the normal dental formula. The prevalence rate of ST varies from 0.5 to 3.8% in the permanent dentition. When ST located distal to the third molar is acclaimed as distomolar. Moreover, kissing molar is an extremely scarce condition of distomolars, pointed in the opposite direction in a single follicular space. Meanwhile, macrodontia is also a rare shape anomaly characterized by a large crown and tapering root. Case pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
4
1
3
Order By: Relevance
“…The causes and characteristics of KMs are mysterious. There are some reported cases of KMs in patients with mucopolysaccharidosis, supernumerary teeth, and macrodontia [11] [12]. However, our patients had no significant systemic findings.…”
Section: Discussioncontrasting
confidence: 52%
“…The causes and characteristics of KMs are mysterious. There are some reported cases of KMs in patients with mucopolysaccharidosis, supernumerary teeth, and macrodontia [11] [12]. However, our patients had no significant systemic findings.…”
Section: Discussioncontrasting
confidence: 52%
“…O tratamento cirúrgico envolvendo a extração ambos os dentes de KMs é o protocolo de tratamento mais comum (4, 5, 7-10, 13-15, 17-19, 25, 27, 28, 31, 34-37). Outras opções de tratamento compreendem a terapia ortodôntica ( 16) quando há possibilidade de alinhamento dos dentes envolvidos, acompanhamento e proservação do paciente em casos sem sintomatologia e sem espessamento do folículo (8,17,31,33), ou ainda tratamentos combinados, como cirúrgicoortodôntico (17,(38)(39)(40).…”
Section: Tratamentounclassified
“…O tratamento conservador é possível em casos assintomáticos e sem dilatação cística do folículo dental que envolve KMs (10,26), desde que seja aliado ao controle periódico clínicoradiográfico para revisão e avaliação de desenvolvimento de quaisquer patologias relacionadas (40).…”
Section: Tratamento Conservadorunclassified
See 1 more Smart Citation
“…Such cases were frequently noted in maxillary molars, but were rarely found in the mandible, especially in a third molar and a supernumerary fourth tooth [ 2 ]. Previous research studies reported that the incidence of supernumerary fourth molar is 0.32%, not significantly different between the sexes [ 4 ], and the concrescence of teeth shared similar anatomic morphology with normal molars; usually it might not be erupted [ 5 ]. For clinical applications, it is important to establish a normative diagnosis so that proper treatment can be provided at the earliest time possible.…”
Section: Introductionmentioning
confidence: 99%